2011
DOI: 10.1016/j.jcomdis.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurophysiological correlates of striatal dopamine depletion: A rodent model of Parkinson's disease

Abstract: Both limb and cranial motor functions are adversely impacted by Parkinson's disease (PD). While current pharmacological and surgical interventions are effective in alleviating general limb motor symptoms of PD, they have failed to provide significant benefit for cranial motor functions. This suggests that the neuropathologies mediating limb and cranial motor impairments in PD may differ. Animal models provide a mechanism by which the potential neural dysfunctions underlying these different motor impairments ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Our finding of decreased tongue force following 6-OHDA is consistent with previous findings using this model and similar methods [13,36,41]. It is interesting to note, however, that in preclinical studies measuring maximal force output, nigrostriatal DA depletion tends to affect tongue force production to a greater extent than forelimb force production in young adult animals [6,13,28,36].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our finding of decreased tongue force following 6-OHDA is consistent with previous findings using this model and similar methods [13,36,41]. It is interesting to note, however, that in preclinical studies measuring maximal force output, nigrostriatal DA depletion tends to affect tongue force production to a greater extent than forelimb force production in young adult animals [6,13,28,36].…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note, however, that in preclinical studies measuring maximal force output, nigrostriatal DA depletion tends to affect tongue force production to a greater extent than forelimb force production in young adult animals [6,13,28,36]. We recently reported that at unilateral striatal DA depletion levels between 40–60%, rats exhibit substantial forelimb force control deficits, but not decreased force production [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe striatal dopamine loss following 6-OHDA infusions results in more predictable and reliable deficits to the limb sensorimotor system compared to aspects of cranial (oromotor) function, such as licking and chewing,[25-27] suggesting that these two systems may have a different sensitivity to dopamine depletion. However, the relationships among behavioral measures of lesion severity in the limb, such as forelimb use and apomorphine rotations, and ultrasonic vocalizations are unknown, particularly with mild dopamine depletion.…”
Section: Introductionmentioning
confidence: 99%